ChemInform Abstract: Cascade Palladium‐ and Copper‐Catalyzed Aromatic Heterocycle Synthesis: The Emergence of General Precursors. Issue 21 (2nd May 2013) - Ball, Catherine J.; Willis, Michael C.
Abstract Review: 101 refs.